2021
DOI: 10.1186/s13007-021-00748-z
|View full text |Cite
|
Sign up to set email alerts
|

A handheld device for measuring the diameter at breast height of individual trees using laser ranging and deep-learning based image recognition

Abstract: Background Accurate and efficient measurement of the diameter at breast height (DBH) of individual trees is essential for forest inventories, ecological management, and carbon budget estimation. However, traditional diameter tapes are still the most widely used dendrometers in forest surveys, which makes DBH measurement time-consuming and labor-intensive. Automatic and easy-to-use devices for measuring DBH are highly anticipated in forest surveys. In this study, we present a handheld device for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In recent years, the application of deep learning algorithms, such as convolutional neural networks, has improved the convenience and accuracy of image recognition and segmentation in different fields, such as face mask detection [ 33 ], classification of magnetic resonance images [ 34 ], X-ray images [ 35 ], and tree trunk identification [ 36 ]. The performance of deep learning has proven to be superior to other classical methods of computer vision [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the application of deep learning algorithms, such as convolutional neural networks, has improved the convenience and accuracy of image recognition and segmentation in different fields, such as face mask detection [ 33 ], classification of magnetic resonance images [ 34 ], X-ray images [ 35 ], and tree trunk identification [ 36 ]. The performance of deep learning has proven to be superior to other classical methods of computer vision [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It yields results which are close to state of the art or better in many areas [27]. These technologies are used in image recognition, real-time translations, voice recognition services such as Siri from Apple, Alexa from Amazon, and Cortana from Microsoft [28,29]. In addition, multiple studies have shown that DL algorithms are state of the art in breast histopathology analysis, skin cancer classification, risk of cardiovascular disease prediction, the detection of lung cancer, and several applications in the ophthalmic area with the potential to revolutionize the diagnosis of eye diseases [30][31][32].…”
Section: Introductionmentioning
confidence: 88%
“…We developed a device based on image sensor and laser module to estimate SD of individual tree and evaluate the accuracy of measurements by comparing their corresponding field measurements. Different from the work of Fan et al [44] and Song et al [37], the collimated beam emitted by the laser module keeps the spot shape constant in natural scenes and can be used as a reference and anchor point. Image sensor can retain texture and shape features in images.…”
Section: Characteristics Of the Devicementioning
confidence: 98%
“…The measured DBH produced RSM E is 2.17 mm and M AE is 15.10 mm. Song et al [37]. constructed an integrated device of digital camera and LiDAR and RM SE of measured DBH is 3.07 mm and BIAS is 0.06 mm.…”
Section: The Analysis Of Major Error Sourcesmentioning
confidence: 99%
See 1 more Smart Citation